2008
DOI: 10.1111/j.1600-0501.2007.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

In‐patient comparison of immediate and conventional loaded implants in mandibular molar sites within 12 months

Abstract: In the present study, immediate functionally loading did not negatively affect implant stability, marginal bone levels and peri-implant health when compared with conventional loading of single-tooth implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
1
30
1
Order By: Relevance
“…When Group I was compared to Group II, there was no significant change in the mean radiographic bone loss which is in accordance with the study conducted by Güncü et al . [23] in 2008 that immediate loading did not negatively affect implant stability, marginal bone levels, and peri-implant health when compared with CL. Furthermore, Schingalia et al .…”
Section: Discussionmentioning
confidence: 99%
“…When Group I was compared to Group II, there was no significant change in the mean radiographic bone loss which is in accordance with the study conducted by Güncü et al . [23] in 2008 that immediate loading did not negatively affect implant stability, marginal bone levels, and peri-implant health when compared with CL. Furthermore, Schingalia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies comparing immediately or delayed loaded implants in the posterior region have shown slightly lower survival rates for immediately loaded implants. 22,23 Furthermore, Schincaglia et al 23 have observed that the radiographic bone level for immediately loaded implants is significantly lower than that reported for delayed loaded implants. However, long-term studies are needed to confirm these results.…”
mentioning
confidence: 95%
“…12 Guncu et al showed that immediate functional loading did not negatively affect implant stability, marginal bone levels, and peri-implant health. 14 lesser than conventionally loaded implant. 15 Rousseau 16 concluded that a patient eligible for flapless surgery can benefit from less straining procedure without affecting the success rate of dental implant surgery.…”
Section: Discussionmentioning
confidence: 93%